TUTORING AS A FORM OF PSYCHOLOGICAL PEDAGOGICAL SUPPORT TO CHILDREN WITH SPECIAL EDUCATIONAL NEEDS - Spirina, Valentina; Kapieva, Knarik; Spirina, Maria; Tupichkina, Elena; Loba, Vsevolod (Revista Inclusiones, 2020)
The importance of the development of giftedness in children, including those with disabilities, is emphasized in the article, the author’s view on understanding the essence of the category of children with special educational needs is revealed, the importance of unlocking the potential, giftedness of a child is emphasized. Based on a brief description of children with disabilities and their giftedness, it is concluded that it is necessary to create individual education and development routes for such children, one of which is psychological and pedagogical support to a child in the form of tutoring. Particular attention is paid to the essence and specifics of tutoring, taking into account foreign experience, issues of training tutors at various levels of education. In conclusion, the authors of the article present the target orientations of a project dedicated to the problem under consideration that is being developed at Armavir State Pedagogical University.